Concepções de infância e a cidade: o estado da arte sobre o espaço e lugar da criança - Bonfim, Ebrain Augusto Calil Bonfim [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
In recent years there has been a significant growth in research called state of the art, not only in Brazil, but in the rest of the world. The present research uses this learning method, seeking to map and discuss, within the scope of school geography and social sciences, the subjects related to the child's relationship and the city. The book named How children see the city served as an inspiration of the theme reached, in the Scientific Electronic Library Online (SCIELO) database, for articles published on the subject in the period from 2016 to 2021. Among our searches, we tried to understand how the articles address the child's relationship with the city? Are there studies that deal with the influence of places on the construction of the child's identity? How has school geography turned to civic education? Our analysis shows that most of the selected texts are experience reports or reflection articles that show a lack of bibliography on the subject

Nos últimos anos houve um crescimento significativo nas pesquisas denominadas estado da arte, não somente no Brasil, mas no resto do mundo. A presente pesquisa utiliza desse método para apresentar um mapeamento e discutir, no âmbito da geografia escolar e das ciências sociais, alguns aspectos das pesquisas que tratam da criança e da sua relação com a cidade. O livro intitulado Como as crianças veem a cidade serviu de inspiração para o tratamento do tema que buscou, no banco de dados Scientific Electronic Library Online (SCIELO) artigos publicados sobre o tema no período de 2016 a 2021. Entre nossas buscas, procuramos compreender como os artigos abordam a relação da criança com a cidade? Há estudos que tratam da influência dos lugares na construção da identidade da criança? Como a geografia escolar tem se voltado para a formação cidadã? Nossa analise evidencia que a maioria dos textos selecionados são relatos de experiência ou artigos de reflexão que mostram uma carência de bibliografia acerca do tema.
Childhood conceptions and the city: the state of the art on the space and place of the child
Keywords: Student-city relationship; Geographic space; Child and city; Relação aluno-cidade; Espaço geográfico; Criança e cidade